Deep Learning untuk Solusi Cerdas: Workshop Penggunaan Aplikasi AI untuk Kehidupan Sehari-Hari - Netti Herawati; K Ghazali; Uci Suryani; M Bambang Purwanto (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity is motivated by the rapid development of deep learning and artificial intelligence (AI) which has penetrated various aspects of life. Prasetiya Mandiri Polytechnic held a workshop "Deep Learning for Smart Solutions: Workshop on the Use of AI Applications for Daily Life" to increase AI literacy among students and lecturers. The method of implementing this activity includes the preparation of workshop materials, the implementation of presentation sessions, discussions, and practical exercises, as well as evaluation through questionnaires and observations. The results of the activity showed high enthusiasm of participants and increased understanding of the basic concepts of deep learning and AI applications. The interpretation of the questionnaire data showed a high level of participant satisfaction, with an average score of 4.5 on a scale of 5. The results of the participants' practical exercises also demonstrated their ability to apply AI concepts to create simple applications. This activity succeeded in achieving its goal of improving participants' digital skills and encouraging the application of AI in learning and research at Prasetiya Mandiri Polytechnic. In conclusion, this workshop is effective in improving AI literacy and providing practical experience to participants, and has the potential to be further developed by adding more intensive and diverse practice sessions